“He Burned Out Like a Candle.” John Reed in Revolutionary Russia: American and Soviet Screen Images - Evgenii V. Volkov (Historia provinciae: журнал региональной истории)
The author of the article analyzes the images of journalist and writer John Reed in the feature films Reds (1981) by Warren Beatty and Red Bells (1982) by Sergei Bondarchuk as the “texts” of cultural memory represented in the cinema that convey the ideas of the past. The author of the article emphasizes that when making historical films, cineastes are influenced by the images of literature, fine arts, and theater as well as by the knowledge of the past presented in the works of historians. The attitudes prevailing in society and the official state ideology play no lesser role in the process. First, the paper briefly characterizes the images of John Reed presented in the works of artist I. Brodskii, Soviet and English historiography, and some productions of the USSR theaters and feature films. Then the article considers the process of preparation and creation of Warren Beatty’s Reds and the response of American audience to it. It is followed by the description of the preparation and work on the film Red Bells by Sergei Bondarchuk and the way it was received by the Soviet viewers. The history of making the both films (the 1970s – early 1980s) is examined in the context of the Cold War. In the context of American and Soviet collective identity, the images of the American journalist and writer presented on the screen in these films were different. The personality of John Reed in the American version is characterized by individuality, dramatics, and contradictory characteristics. To make the movie more convincing, Warren Beatty conducted and filmed a number of interviews and then included in his movie the episodes that contained oral testimonies of John Reed’s contemporaries with their contradictory interpretations and assessments. The Soviet film, created within the official Soviet discourse on the Great October Socialist Revolution, presents John Reed as a fighter for the ideals of the revolution in the collective of fellow Bolsheviks. While the American film ends tragically with John Reed’s death from typhoid fever in Soviet Russia, the Soviet film, full of optimism, makes no mention of this event.